Biosintesis Nanopartikel Perak menggunakan Ekstrak Daun Ketapang, Modifikasi dengan Asam p-kumarat untuk Aplikasi Deteksi Melamin - Rusnaenah, Andi; Zakir, Muhammad; Budi, Prastawa (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2017)
Biosynthesis of silver nanoparticles (AgNPs) using ketapang leaf extract, modification with p-coumaric acid for detecting melamine has conducted. This research aimed to synthesize AgNPs via bio-reduction method using ketapang leaf extract followed by modification with p-coumaric acid (APK), and evaluating its application detecting melamine. The AgNPs were characterized through ultraviolet-visible absorption spectroscopy (UV-Vis) and X-ray diffraction (XRD). Observation suggested that an increase of incubation time had affected its surface Plasmon resonance trend. Further analysis of crystallite via XRD suggested that nanoparticle size at 43 nm estimated using Debye-Scherer, within the form of unit cells is cubic. The performance of product as melamine detector suggested that the AgNPs-APK had detected melamine in range of concentration from 0.1 to 1000 ppm.